2004
DOI: 10.1111/j.1572-0241.2004.40175.x
|View full text |Cite
|
Sign up to set email alerts
|

Is Esophageal pH Monitoring Used Appropriately in an Open-Access System? A Prospective Multicenter Study

Abstract: In an open-access system, a high proportion of esophageal pH studies are done for indications not consistent with published guidelines, particularly among the examinations not requested by gastrointestinal specialists. Further education is still needed on the appropriate use of esophageal pH monitoring and management of gastroesophageal reflux disease (GERD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In a prospective multicenter study done in Italy and published in 2004, only 323 examinations (38%) performed were for appropriate indications, and the vast majority for pH monitoring indications were inconsistent with the guidelines. 31 In contrast, Ali, et al found that that pH monitoring is underutilized in the evaluation of persistent GERD symptoms after anti-reflux surgery. 32 …”
Section: Diagnostic Testing and Endoscopic Interventionsmentioning
confidence: 99%
“…In a prospective multicenter study done in Italy and published in 2004, only 323 examinations (38%) performed were for appropriate indications, and the vast majority for pH monitoring indications were inconsistent with the guidelines. 31 In contrast, Ali, et al found that that pH monitoring is underutilized in the evaluation of persistent GERD symptoms after anti-reflux surgery. 32 …”
Section: Diagnostic Testing and Endoscopic Interventionsmentioning
confidence: 99%